ANALISIS NERACA AIR BERSIH DUSUN JOBEN DESA PESANGGRAHAN KECAMATAN MONTONG GADING KABUPATEN LOMBOK TIMUR TAHUN 2024 - Anisa, Siti; muhammad iman, darmawan (Jurnal Teknologi Lingkungan, 2025)
The limited availability of clean water, unable to meet the ever-increasing demand, raises concerns for the community. Therefore, an analysis of the clean water balance is necessary to ensure an adequate water supply. This study aims to calculate the availability of clean water, assess water needs, and analyze the clean water balance in Joben Hamlet, Pesanggrahan Village, Montong Gading Subdistrict, East Lombok Regency, in 2024. The research method used was a descriptive quantitative approach, with data comprising primary and secondary sources. Data collection techniques include observation, direct field measurements, interviews with local residents, and documentation related to water resources in the area. Data analysis techniques involve calculating water availability, water needs, and the status of the water balance in the hamlet. The study results show that the primary water sources in Joben Hamlet come from springs, rivers, water reservoirs, and groundwater. These sources were sufficient to meet domestic and non-domestic water needs. The water requirement per household is calculated to be 165 liters/day, assuming an average household size of five people, each needing 33 liters per day. The total domestic need for 226 households amounts to 37,290 liters per day. The total water availability recorded over one day is 3,457,368.248 liters, while the water requirement is only 1,767.227 liters. Thus, there is a surplus of 3,455,601.02 liters per day. This balance indicates that the area still has abundant water resources, capable of meeting future community needs and supporting other economic sectors.